Accountability in Islamic Law for Damage or Loss of Goods in Service Transactions: A Systematic Literature Review - Dimas Iin Ricky Prasetiyo; Wargo; Kurniawan; Iwan Aprianto (Zabags International Journal of Islamic Studies, 2025)
This article examines the accountability of service providers in cases of loss or damage to goods from the perspective of Islamic law. The study aims to analyze the extent to which classical jurisprudence and contemporary scholarship offer a coherent foundation for resolving modern service-related issues. Employing a systematic literature review approach, data were gathered from open-access journal publications, focusing on works that specifically address the principles of amanah (trust) and daman (liability) within contractual frameworks. The review identifies several thematic categories, including the interpretation of accountability in classical texts, the application of liability in financial and logistics services, and the adaptation of shariah principles in contemporary service sectors. Findings reveal that accountability in Islamic law not only concerns contractual obligations but also embodies ethical and spiritual responsibilities, thereby reinforcing the protection of consumer rights in alignment with the objectives of maqasid al-shariah. The study contributes to the development of academic discourse on liability and accountability in Islamic jurisprudence while providing practical insights for policymakers and service providers in formulating fair and shariah-compliant service agreements.